At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the value of the piecewise function [tex]\( f(x) \)[/tex] when [tex]\( x = 3 \)[/tex], let's analyze the conditions given in the definition of the piecewise function:
[tex]\[ f(x) = \begin{cases} -x, & \text{if } x \leq -1 \\ 1, & \text{if } x = 0 \\ x + 1, & \text{if } x \geq 1 \end{cases} \][/tex]
We are tasked with finding [tex]\( f(3) \)[/tex]. Let's match [tex]\( x = 3 \)[/tex] with the appropriate condition from the piecewise function definition:
1. For [tex]\( x \leq -1 \)[/tex]:
[tex]\[ f(x) = -x \][/tex]
This condition does not apply because [tex]\( 3 \)[/tex] is not less than or equal to [tex]\(-1\)[/tex].
2. For [tex]\( x = 0 \)[/tex]:
[tex]\[ f(x) = 1 \][/tex]
This condition does not apply because [tex]\( 3 \)[/tex] is not equal to [tex]\( 0 \)[/tex].
3. For [tex]\( x \geq 1 \)[/tex]:
[tex]\[ f(x) = x + 1 \][/tex]
This condition applies because [tex]\( 3 \)[/tex] is greater than or equal to [tex]\( 1 \)[/tex].
Since [tex]\( x = 3 \)[/tex] satisfies the third condition, we use the formula [tex]\( f(x) = x + 1 \)[/tex]:
[tex]\[ f(3) = 3 + 1 = 4 \][/tex]
Therefore, the value of [tex]\( f(3) \)[/tex] is [tex]\( 4 \)[/tex]. The corresponding answer is:
[tex]\[ \boxed{4} \][/tex]
[tex]\[ f(x) = \begin{cases} -x, & \text{if } x \leq -1 \\ 1, & \text{if } x = 0 \\ x + 1, & \text{if } x \geq 1 \end{cases} \][/tex]
We are tasked with finding [tex]\( f(3) \)[/tex]. Let's match [tex]\( x = 3 \)[/tex] with the appropriate condition from the piecewise function definition:
1. For [tex]\( x \leq -1 \)[/tex]:
[tex]\[ f(x) = -x \][/tex]
This condition does not apply because [tex]\( 3 \)[/tex] is not less than or equal to [tex]\(-1\)[/tex].
2. For [tex]\( x = 0 \)[/tex]:
[tex]\[ f(x) = 1 \][/tex]
This condition does not apply because [tex]\( 3 \)[/tex] is not equal to [tex]\( 0 \)[/tex].
3. For [tex]\( x \geq 1 \)[/tex]:
[tex]\[ f(x) = x + 1 \][/tex]
This condition applies because [tex]\( 3 \)[/tex] is greater than or equal to [tex]\( 1 \)[/tex].
Since [tex]\( x = 3 \)[/tex] satisfies the third condition, we use the formula [tex]\( f(x) = x + 1 \)[/tex]:
[tex]\[ f(3) = 3 + 1 = 4 \][/tex]
Therefore, the value of [tex]\( f(3) \)[/tex] is [tex]\( 4 \)[/tex]. The corresponding answer is:
[tex]\[ \boxed{4} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.